Membrane permeabilization and perturbation induced by alkyl- biguanidium salts. Issue 3 (4th March 2019) - Hébert, Audrey; Parisotto, Maxime; Ferbeyre, Gerardo; Schmitzer, Andreea R.
ABSTRACT: Alkylbiguanidium salts show membrane perturbing properties toward simple phospholipid bilayer (liposomes) and complex phospholipid membranes (bacterial membranes). Compared to metformin and phenformin, alkylbiguanidium salts induce a more significant permeabilization of the phospholipid membranes, leading to highly selective H + /OH − ion transport and subsequent depolarization of the membrane. Although alkylbiguanidium salts with shorterC6 andC8 chains are too hydrophilic to be inserted into the membrane and perturb it, those withC10, C12, C14, andC16 alkyl chains show high membrane permeabilization and depolarization activity. In addition, theC10, C12, andC14 compounds possess interesting antimicrobial activity, and, at concentrations close to their minimal inhibitory concentrations, they show low hemolytic activity and toxicity. Graphical Abstract: